Assessment of the factors contributing to non- adherence of anti- retroviral therapy (ART) treatment among male patients at Katutura Health Centre, Khomas region - Maano, Nghitanwa Emma; Elina N, Niilonga (International Journal of Health, 2017)
The purpose of this study was to assess and explore the contributing factors of non- adherence among male patients on Antiretroviral therapy (ART) treatment at Katutura Health Centre, Khomas Region. The objectives of this study were to determine and describe the factors contributing to non-adherence of ART treatment among male patients at Katutura Health Centre .Data were collected using the structured questionnaires.A purposive sampling technique was used. The collected data were entered in data sets and analyzed using Statistical (SPSS) version 23.0 software to describe the phenomena and to assess the magnitude of ART non-adherence among male patients.The study concluded that non-adherence of ART treatment among male patients in Katutura Health Centre, Khomas region is caused by different factors, such as, lack of food among patients on ART treatment, lack of transportation to the health facility for treatment and alcohol abuse. Therefore practical preventative interventions such as community education program should be developed and implemented to improve and ensure ART adherence.